Augmented Reality in Dentistry: Uses and Applications in the Digital Era - Al-Khaled, Israa; Al-Khaled, Alaa; Abutayyem, Huda (Edelweiss Applied Science and Technology, 2021)
Introduction: With all the advancements that technology has reached, Dentistry can't be left behind. In the past few years, researchers have focused on emerging technologies like Virtual and Augmented Reality with clinical practice. Objectives: This literature review aims to provide an update on the latest technological applications and development in augmented reality in the dental field. Methods: The PubMed database was reviewed, and the studies that fulfilled the inclusion criteria in the last 20 years, from 2000 to 5 May 2020, were included. Results: The search results revealed a total of 72 articles, 32 were excluded, while 40 articles were included. It’s been observed that augmented reality application is still under testing, as certain drawbacks still tie the spread of this technology in the dental field. Multiple studies have resulted in a system that is suitable for clinical use. Yet no routine clinical application has been reported. Conclusion: The research department has already covered more advanced technologies like mixed reality. Therefore, a question arises, whether augmented realty will continue to grow independently or will mixed reality dominate the field.